2005
DOI: 10.1523/jneurosci.4701-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Hydrogen Peroxide Regulates the Excitability of Midbrain Dopamine Neurons via ATP-Sensitive Potassium Channels

Abstract: ATP-sensitive K+(KATP) channels link metabolic state to cell excitability. Here, we examined regulation of KATPchannels in substantia nigra dopamine neurons by hydrogen peroxide (H2O2), which is produced in all cells during aerobic metabolism. Blockade of KATPchannels by glibenclamide (100 nm) or depletion of intracellular H2O2by including catalase, a peroxidase enzyme, in the patch pipette increased the spontaneous firing rate of all dopamine neurons tested in guinea pig midbrain slices. Using fluorescence im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
213
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(229 citation statements)
references
References 69 publications
16
213
0
Order By: Relevance
“…Further distinctions are seen in expression of ATPsensitive potassium (K ATP ) channels, which contribute to the greater effect of DA-selective neurotoxins on SNc versus VTA DA neurons [104]. Moreover, differences in K ATP channel subtypes between two populations of DA neurons within SNc contribute to the relative responsiveness of these cells to metabolic stress and to H 2 O 2 [105,106]. Differences in Ca 2þ channel expression among DA neuron populations is also well recognized, with a greater role for Cav1.3 L-type Ca 2þ channels in the regulation of pacemaker activity in SNc versus VTA DA neurons that contributes to the greater vulnerability of SNc cells to degeneration [107].…”
Section: Dopamine Neuron Anatomy Biochemistry and Physiologymentioning
confidence: 99%
“…Further distinctions are seen in expression of ATPsensitive potassium (K ATP ) channels, which contribute to the greater effect of DA-selective neurotoxins on SNc versus VTA DA neurons [104]. Moreover, differences in K ATP channel subtypes between two populations of DA neurons within SNc contribute to the relative responsiveness of these cells to metabolic stress and to H 2 O 2 [105,106]. Differences in Ca 2þ channel expression among DA neuron populations is also well recognized, with a greater role for Cav1.3 L-type Ca 2þ channels in the regulation of pacemaker activity in SNc versus VTA DA neurons that contributes to the greater vulnerability of SNc cells to degeneration [107].…”
Section: Dopamine Neuron Anatomy Biochemistry and Physiologymentioning
confidence: 99%
“…Elevated hydrogen peroxide suppresses striatal dopamine release (Avshalumov et al 2005), and excess O&NS is involved in the degeneration of dopaminergic neurons (Tsang and Chung 2009).…”
Section: How Oandns and Inflammation Might Influence Biological Pathwaymentioning
confidence: 99%
“…21 It can also be amplified by irreversible inhibition of peroxidase enzymes, and can lead to K ATP channel opening and suppression of axonal DA release. 22 Furthermore, in vivo studies investigating acute exposure to rotenone have shown increased generation of ROS during DA metabolism in nigrostriatal neurons. 21 32 In this work, the carbon-fiber electrode was positioned in the dorsal striatum of an anesthetized rat and ramped from −0.4 to 1.4 V in a triangular waveform every 100 ms at a scan rate of 400 V/s.…”
mentioning
confidence: 99%